Perceived psychosocial stressors and coping resources in chronic low back pain patients as classified by the avoidance-endurance model - Fehrmann, Elisabeth; Fischer-Grote, Linda; Kienbacher, Thomas; Tuechler, Kerstin; Mair, Patrick; Ebenbichler, Gerold (Frontiers in Rehabilitation Sciences, 2022)
Objectives The Avoidance-Endurance Model distinguishes between subgroups of low back pain (LBP) patients with three maladaptive styles of coping with pain: fear-avoidance (FAR), distress-endurance (DER), eustress-endurance (EER), and one adaptive coping style (AR). This study aimed to compare the quantity of patients’ perceived psychosocial stressors and coping resources across these subgroups. Materials and methods This cross-sectional study was conducted at an outpatient rehabilitation center for patients with chronic musculoskeletal pain. One hundred and thirty-seven patients (69 women/68 men) with chronic LBP were assessed using the following: a demographic checklist, the visual analogue scale, Avoidance-Endurance Questionnaire, Roland-Morris Disability Questionnaire, Pain Disability Index, and 36-Item Short Form. Subsequently, patients participated in semi-structured interviews led by clinical psychologists, which were intended to identify their perception of stressors and coping resources. The quantity of psychosocial stressors and coping resources were analyzed using deductive and inductive content analyses and then compared between subgroups using chi-square-tests. Results FARs experienced significantly higher levels of “mental suffering” (p = <.001) and “other workplace problems” compared to ARs and EERs (p = <.001). DERs reported significantly higher levels of “mental suffering” (p = <.001), “job stress” (p = .022), and “familial losses” (p = .029) compared to ARs, whereas the AR group demonstrated significantly more “coping resources” (p = .001) compared to FARs. Conclusion AEM-subgroups differed in the quantity of perceived psychosocial stressors and coping resources with AR, who demonstrated a lower risk for pain chronicity and reported the highest quantity of resources. The variability across subgroups may imply differences in patients´ needs regarding therapeutic interventions and suggests that a resource-centered approach to cope with stress and pain may be beneficial.